The new color code for priority assessment in nursing triage: a pilot study (Dissertation Nursing, 2023)
BACKGROUND:Since the volume of patient admissions in an emergency department (ED) cannot be planned precisely, the available resources can sometimes be overloaded ('crowding'), resulting in risks to patient safety.AIM:The study aimed to evaluate the effectiveness of a new triage evaluation system in the emergency room of an Italian hospital.METHODS:Two-arm pilot study; assignment to the two groups (standard assessment - 4-colour code vs. experimental assessment - 5-colour code) by simple randomisation. Nursing assessments at admission triage were compared with those at dischargeRESULTS:1060 subjects with 'non-traumatic chest pain' and 960 classified as 'acute neurological disorders' were enrolled; the implementation of the new color code allowed a correct assessment of the level of severity in more than 86% of 'cardiological' and 93% of 'neurological' cases; the standard method allowed a correct assessment of less than 83% in cardiological and 77% in neurological cases.CONCLUSIONS:The five-level triage system is a valid method for assessing the severity of incoming patients' conditions by nursing staff in the emergency department. In-depth studies on broader samples are recommended.
Keywords: Triage; Nurses; nurse; assessment; emergency